Characterization of PP/TPV/MMT ternary nanocomposites produced by injection molding - Costantino, Maria A. (2017)
One of the most valued and required features of new polymers are a high level of stiffness combined with good toughness. In this way, it seems useful to combine nanoclay reinforcement with rubber toughening to balance end use performance. In this work, the feasibility of producing this kind of nanocomposites by direct injection molding is evaluated. The performance of actual injected pieces of polypropylene (PP) compounded with thermoplastic vulcanizate (TPV) and organoclay (MMT) is analyzed and compared. Ternary composite presents low warpage and so better final quality. Morphology developed in actual pieces is influenced both by processing and by MMT presence, this morphology giving place to alternative deformation mechanisms and crack arrest. Also, a good impact resistance compared with neat PP is observed. Weld lines are diluted and they do not act as stress concentrators, this being of mechanical and aesthetical interest. The use of PP/TPV/MMT seems to be promising for injected moldings.